Bone healing after Le Fort I osteotomy with SSRO, using uHA/PLLA plates and screws, in class II and III patients. Issue 9 (September 2019) - Ueki, Koichiro; Yoshizawa, Kunio; Moroi, Akinori
Abstract: Purpose: The purpose of this study was to compare bone healing after Le Fort I osteotomy with sagittal split ramus osteotomy (SSRO) in class II and class III patients. Patients and methods: The subjects consisted of 46 Japanese class II and III patients. Le Fort I osteotomy was performed in combination with SSRO. They were divided into two groups (23 class II cases and 23 class III cases). Four absorbable plates (uncalcined and unsintered hydroxyapatite and poly-l -lactic acid — uHA/PLLA) and screws were used to fix the maxillary segment in all patients, in the same manner. Postoperative computed tomography (CT) was analyzed for all patients at 1 week and 1 year postoperatively. The anterior and lateral areas between the maxillary segments were measured using two-dimensional frontal and lateral views from the three-dimensional images reconstructed over a constant CT value. Results: There were no significant differences in the area of bone defect healing between classes II and III at 1 year postoperatively, although there were significant differences between the two groups at 1 week postoperatively ( p  < 0.05). Furthermore, there were no significant differences in the areas of bone defect between 1 week and 1 year postoperatively, in both groups. Conclusion: Using measurements based on CT value threshold within 1 year after Le Fort I osteotomy, this study suggests that the areas of bony defect in the region of the anterior and lateral walls of the maxilla do not always decrease in both classes II and III.